Health Care Professionals' Perceptions about Sensory-Based Interventions in the NICU - Pineda, Roberta; Roussin, Jessica; Heiny, Elizabeth; Smith, Joan (American Journal of Perinatology, 2019)
Objective The main objective of this article is to define perceptions of health care professionals regarding current use of sensory-based interventions in the neonatal intensive care unit (NICU).Study Design A multidisciplinary group of NICU health care professionals (n = 108) defined the types of sensory-based interventions used in their NICU, the postmenstrual age (PMA) sensory-based interventions are administered, conditions under which sensory-based interventions are used, and personnel who administer sensory-based interventions.Results The most commonly reported tactile intervention was infant holding (88% of respondents), the most common auditory intervention was recorded music/singing (69% of respondents), the most common kinesthetic intervention was occupational and physical therapy (85% of respondents), and the most common vestibular intervention was infant swings (86% of respondents). Tactile interventions were initiated most often at 24 to 26 weeks PMA (74% of respondents), auditory interventions at 30 to 32 weeks (60% of respondents), kinesthetic interventions at 30 to 32 weeks (76% of respondents), vestibular interventions at 33 to 34 weeks (86% of respondents), and visual interventions at 32 to 36 weeks (72% of respondents). Conditions under which sensory-based interventions were administered, and personnel who provided them, varied across settings.Conclusion Varied use of sensory-based interventions in the NICU were reported. While this study was limited by biased sampling and the identification of health care professionals' perceptions but not real-world practice, this information can be used to build a comprehensive approach to positive sensory exposures in the NICU.
Keywords: tactile; auditory; engagement; multimodal; stimulation; therapy; outcomes; development; preterm